2022
DOI: 10.12911/22998993/149821
|View full text |Cite
|
Sign up to set email alerts
|

Land Cover Changes and Impacts of Massive Siltation on the Mangrove Segara Anakan Lagoon System, Cilacap Indonesia

Abstract: Changing coastal zones in Indonesia, such as coral reefs, seagrass, and mangroves, have an impact on tropical ecosystems. Excessive exploitation and sedimentation, in particular, have threatened the mangrove at Segara Anakan Cilacap. In order to evaluate temporal land cover changes and the impact of high siltation on the Segara Anakan lagoon system in Cilacap, Indonesia, a research was conducted. The land cover data from SPOT 4 was available in 2008, and the Sentinel-2A data was available in 2019. The Normaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In the eastern part of the research location, various mangrove species were found, including Aigeceras, Ceriops, Rhizopora, and Nypa. Conversely, in the western part, mangrove species from the Acanthus and Derris groups are prevalent [18,19,20]. The region experiences two distinct seasons, namely the wet and dry seasons, which occur from October to May and from July to September, respectively.…”
Section: Research Areamentioning
confidence: 99%
“…In the eastern part of the research location, various mangrove species were found, including Aigeceras, Ceriops, Rhizopora, and Nypa. Conversely, in the western part, mangrove species from the Acanthus and Derris groups are prevalent [18,19,20]. The region experiences two distinct seasons, namely the wet and dry seasons, which occur from October to May and from July to September, respectively.…”
Section: Research Areamentioning
confidence: 99%
“…The mangroves in Segara Anakan Cilacap are the only ones that are not in a conservation area and are found in almost the entire area. The western part of the area was converted into residential areas, while the eastern part of the area was used as an industrial area and a small area for aquaculture (Ardli et al, 2022).…”
Section: Introductionmentioning
confidence: 99%